2016
DOI: 10.1039/c6ra15545f
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activities of phosphonium containing polynorbornenes

Abstract: In this study, amphiphilic polyoxanorbornene with different alkyl and aromatic phosphonium side chains was synthesized and investigated their biocidal properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…[1] Drug development strategies inspired by antimicrobial peptides (AMPs) have been explored. [3] In response,synthetic, membrane-inserting mimics have been developed that capture some of the essential functions of AMPs,w hile overcoming certain limitations.E xamples include arylamide oligomers, [4] polynorbornenes, [5] polyme-thacrylates, [6] and an emerging class referred to as conjugated oligoelectrolytes (COEs). [3] In response,synthetic, membrane-inserting mimics have been developed that capture some of the essential functions of AMPs,w hile overcoming certain limitations.E xamples include arylamide oligomers, [4] polynorbornenes, [5] polyme-thacrylates, [6] and an emerging class referred to as conjugated oligoelectrolytes (COEs).…”
mentioning
confidence: 99%
“…[1] Drug development strategies inspired by antimicrobial peptides (AMPs) have been explored. [3] In response,synthetic, membrane-inserting mimics have been developed that capture some of the essential functions of AMPs,w hile overcoming certain limitations.E xamples include arylamide oligomers, [4] polynorbornenes, [5] polyme-thacrylates, [6] and an emerging class referred to as conjugated oligoelectrolytes (COEs). [3] In response,synthetic, membrane-inserting mimics have been developed that capture some of the essential functions of AMPs,w hile overcoming certain limitations.E xamples include arylamide oligomers, [4] polynorbornenes, [5] polyme-thacrylates, [6] and an emerging class referred to as conjugated oligoelectrolytes (COEs).…”
mentioning
confidence: 99%
“…Most of the cases M n determined by GPC was underestimated compared to values derived by NMR end group analysis . Suer et al also observed same phenomenon for polar phosponiumbased ROMP polymer . GPC calibration with linear, non‐ionic pullulan standards resulted in different hydrodynamic volumes with respect to the cationic‐based copolymers, which can lead to a strong deviation .…”
Section: Resultsmentioning
confidence: 83%
“…Compared to these findings, when the alkyl group was longer, that is the increasing hydrophobicity, the polymers turned out to be effective and generally toxic . It was also observed that cationic charge density treshold also crucial for the activity against to S. aureus . Increasing the double charge density in each repeating unit resulted in high selectivity.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations